Identification of Leaf Disease based on Artificial Intelligence - G, Manoj Kumar; S , Girirajan (International Journal of Psychosocial Rehabilitation, 2020)
Now a days, identification of diseases in plants has become very difficult in the agriculture field. Having malady in plants is quite natural, but if correct measures and care aren’t taken, then it causes adverse effects on plants. These effects may reduce the product quality as well as productivity. Since agriculture has been contributing a lot to the Indian economy, it is important to automate the identification and detection of plant diseases. In our paper, the ML model makes use of transfer learning. We used Teachable Machine, a web-based tool that makes creating ML models fast and easy. The new version, Teachable Machine 2.0, makes AI easier for everyone. It builds a light-weight network based on MobileNetV2. It performs deep learning tasks directly on the clients for better privacy and timely response (browsers). Along with advancements in computer vision and increasing smartphone use made possible via deep learning, they paved the way for smart-assisted disease diagnosis. The trained model achieves an accuracy of 99% on the testing dataset.